The psychological barriers for higher education students’ ability of giving at Salahuddin University - Amin, Salwa Ahmed (Zanco Journal of Human Sciences, 2020)
This study aims to identify the psychological barriers for higher education students’ ability of giving at Salahuddin University. To achieve this aim، the researcher utilizes Shaqeer’s Scale (2002) for psychological barriers (35 items) and Raheem’s scale (2017) for the ability of giving (30 items). The two scales were sent to experts to check face validity، which calculated as (0.87) for the ability of giving scale and (0.82) for the psychological barriers scale. Due to this high level of validity، the two scales were adopted as are without making any change in the items. As for reliability issues، Alpha Chronbach coefficient was used to check the internal consistency of the two scales، which were estimated as (0.92) for the ability of giving scale and (0.90) for the psychological barriers scale. Hence، the researcher ensured that the two scales were highly reliable. The results revealed that there is a significant relationship between the students’ ability of giving and the psychological barriers that they encounter at higher education level. Finally، the researcher puts forward some recommendations and suggestions based on the results of the study.